EVALUASI PELAKSANAAN KEBIJAKAN PENGEMBANGAN USAHA AGRIBISNIS PERDESAAN (PUAP) DI KECAMATAN BATANG KABUPATEN BATANG - Nisma Okidah; Budi Setiyono; Turtiantoro . (Journal of Politic and Government Studies, 2015)
Study on Evaluation of Rural Agribusiness Development Policy (PUAP) in the District of Batang, Batang county is a fairly interesting discussion in line with the policies of poverty alleviation in rural areas.Developing countries such as Indonesia have major problems, namely poverty and unemployment, especially in rural areas. Therefore, the Ministry of Agriculture of the Republic of Indonesia issued Regulation of the Minister of Agriculture No. 16 / Permentan / OT.140 / 2/2008 on February 11, 2008 on general guidelines for Rural Agribusiness Development (PUAP) to overcome the limitation of capital sources for farmers. In the framework of the implementation of PUAP Minister of Agriculture has established a Rural Agribusiness Development Team of the Minister of Agriculture No. 545 / Kpts / OT.160 / 9/2007. Batang district is the recipient of funds. In the implementation of the Rural Agribusiness Development Policy (PUAP) also implemented by the Denasri Wetan sub district, Kasepuhan sub district, and Sambong sub district. The activities of the Rural Agribusiness Development Policy (PUAP) are savings and loans. Therefore, the formulation of the problem in this research is "How do the Implementation of Rural Agribusiness Development Policy (PUAP) Denasri Wetan sub district, Kasepuhan sub district, and Sambong sub district?" And "What are the factor that support and obstacle in the implementation of developing an Agribusiness rural areas (PUAP) policy in Denasri Wetan sub district, Kasepuhan sub district, and Sambong sub district? ".This type of research is a qualitative descriptive type. The primary data source was obtained through interviews, observation, and documentation and secondary data sources obtained from the archives, books, journals and other sources. Mechanical analysis with analysis from various sources, data reduction, until the conclusion according to the results obtained from the field.From the results of research conducted by the author, the conclusion that can be drawn from this study are: first, PUAP policy implemented by the 162 villages and sub-districts in Batang. In the study sites, Denasri Wetan sub district is categorized very good in the implementation of policies, but both of the comparative sub-districts such as Kasepuhan sub district and Sambong sub district are still developing and encountering some obstacles in its implementation. Second, supporting factors and obstacles of implementing the Policy Board PUAP derived from Gabungan Kelompok Tani (Gapoktan) and the user community themselves.Advice that can be given by author to relevant agencies namely the Executive Agency and the Food Security Extension (BP2KP) and Supervisor Mitra Tani (PMT) are continuing to improve, maintain performance and cooperation between actors in the monitoring and evaluating of policies PUAP Gapoktan organizers and together provide the best solutions to the problems that arise in the field. Whereas, recommendation for further research is the author can analyze the user community dependence Direct Community Assistance (BLM) PUAP toward PUAP funds from the government.